An exploratory evaluation of dramatherapy in a key stage 3 and 4 pupil referral unit: a multiple case study design - Wörsching, Anna (2014)
This thesis presents an exploratory case study evaluation of a dramatherapy intervention in a key stage three and four pupil referral unit for permanently excluded young people. Dramatherapy is a creative arts therapy concerned with the relationship between the therapist and the client using the medium of drama or theatre to make sense of life experiences (Landy, 2006). Existing literature suggests that this is a relatively under-researched topic, and there is a need for evidence-based practice to support the use of dramatherapy (Dokter, Holloway & Seebohm, 2011). Through continued engagement with the literature and subsequently the participants and dramatherapists, the research began to take more of an exploratory path, investigating whether change had occurred in dramatherapy and if so why this could have happened. This change was reflected in the research questions. The research questions focused on the perceived changes that were observed by the participants themselves, their dramatherapists or a member of school staff during the period of the intervention; if changes were perceived what within the intervention could have helped bring the changes about, and what factors external to dramatherapy could have influenced the process of the intervention.